Identification of soil microorganisms phosphate mineralizers - Barea, J. M.; Ramos, A.; Callao, V. (Ars Pharmaceutica (Internet), 1969)
We have made a study of the morfological, cultural and staining characters as well as a selection of biochemical test wich are of general usefulnes in the identification of bacteria, to investigate the genus of 50 soil strains mineralizing of organic phosphates. The mineralizing strains identified are included in the genera Bacillus (28%), Pseudomonas (28%), Aerobacter, Aeromonas, Acinetobacter, Flavobacterium, Achromobacter, Xanthomonas, Streptomyces, Sarcina, Micrococcus, Kurthia and soil coryneforms.